SOSIAL EKONOMI POLA AGROFORESTRI DI SUB DAS LAHUMBUTI HULU KABUPATEN KONAWE PROPINSI SULAWESI TENGGARA - Agus Setiawan; La Ode Agus Salim Mando; Muh. Dassir; Yusran Yusran (Jurnal Ecogreen, 2015)
Population growth has substantially led to the need of food and land, both in the dry region or in the hilly area.  This study aims to determine the application of agroforestry patterns, income levels and social characteristics of agroforestry farmers in Sub-watershed upstream Lahumbuti. The study was conducted in June till September 2013 in Sub-watershed upstream Lahumbuti. The site was selected through the application of research purposive sampling preceded with field observations then stratified based on species composition, vegetation structure and cropping patterns. The data obtained were then analyzed qualitatively and quantitatively according to the type of data and research purposes. The data was collected through in depth interviews and survey methods. The analytical method used is the analysis of the functional characteristics and analysis of farming. The results indicated that the application of the patterns of agroforestry farmers with agrisilvikultur system that is a combination of agricultural crops and forestry, plantation and forestry and agricultural crops, plantations and forestry. A pattern of agroforestry land productivity contributes the highest income level at IDR. 22.910.000, ha/year.  Moreover, the pattern has a high social value supported by the considerable labor and more intensive farming activities  Keywords : Patterns, watersheds, land use, Konawe.